Technology and readout for scaling up superconducting nanowire single-photon detectors - Knehr, Emanuel Marius (Karlsruher Schriftenreihe zur Supraleitung, 2023)
This work presents three advances to scale SNSPDs from few-pixel devices to large detector arrays: atomic layer deposition for the fabrication of uniform superconducting niobium nitride films of few-nanometer thickness, a frequency-multiplexing scheme to operate multiple detectors with a reduced number of lines, and the integration of SNSPDs with free-form polymer structures to achieve efficient optical coupling onto the active area of the detectors.